Local mRNA translation and cytoskeletal reorganization: Mechanisms that tune neuronal responses - Triantopoulou, Nikoletta; Vidaki, Marina (Frontiers in Molecular Neuroscience, 2022)
Neurons are highly polarized cells with significantly long axonal and dendritic extensions that can reach distances up to hundreds of centimeters away from the cell bodies in higher vertebrates. Their successful formation, maintenance and proper function, highly depends on the coordination of intricate molecular networks that allow axons and dendrites to quickly process information, and respond to a continuous and diverse cascade of environmental stimuli, often without enough time for communication with the soma. Two seemingly unrelated processes, essential for these rapid responses, and thus neuronal homeostasis and plasticity, are local mRNA translation and cytoskeletal reorganization. The axonal cytoskeleton is characterized by high stability and great plasticity; two contradictory attributes that emerge from the powerful cytoskeletal rearrangement dynamics. Cytoskeletal reorganization is crucial during nervous system development and in adulthood, ensuring the establishment of proper neuronal shape and polarity, as well as regulating intracellular transport and synaptic functions. Local mRNA translation is another mechanism with a well-established role in the developing and adult nervous system. It is pivotal for axonal guidance and arborization, synaptic formation and function, and seems to be a key player in processes activated after neuronal damage. Perturbations in the regulatory pathways of local translation and cytoskeletal reorganization contribute to various pathologies with diverse clinical manifestations, ranging from intellectual disabilities to autism spectrum disorders and schizophrenia. Despite the fact that both processes are essential for the orchestration of pathways critical for proper axonal and dendritic function, the interplay between them remains elusive. Here we review our current knowledge on the molecular mechanisms and specific interaction networks that regulate and potentially coordinate these interconnected processes.